Pest management and pesticide used in some Hospitals of Benghazi - Garboui, S.; Elbagrmi, T.; Elbagrmi, T. (Libyan Journal of Science &Technology, 2022)
Public health pest management involves the control of insects or other vectors that transmit diseases to humans. These pests include mosquitoes, cockroaches, bedbugs and domestic rodents. Chemical pesticides assisted in containing the spread of infection and helped reduce infestations with pests. On the other hand, it may have a high-risk acute toxicity and/or chronic effects, which are dangerous, especially to children. Furthermore, they can cause cancer, neurologic damage, delayed development, reproductive dysfunction, and death in many parts of the world, generally through occupational exposure and accidental poisoning of patients. The current study was based on public hospitals in Benghazi city of Libya using questionnaires to collect data in 2013 and then completed in 2015-2016. The results showed a high level of infestation in the hospitals that were studied. The major insect pest species was the German cockroach (Blattella germanica). Insect control agents containing permethrin, cypermethrin, deltamethrin were used. In addition to different formulations such as baits, traps, gel baits that contain hydramethylnon, imidacloprid, chlorpyriphos. The study acknowledges the benefits those pesticides carried out to hospitals, but also understanding their potential harm and side effects. The most important finding is that pesticides are used extensively in Benghazi’s hospitals. More than 15 different pesticides are presently applied in hospitals, such as fog, spray, and powder pesticides. They are applied in mostly all areas, including areas that contain patients. On the bright side, the study finds that hospitals in Benghazi have started to use less toxic pesticides and try to use other pesticides in safe ways.